2020
DOI: 10.1088/1475-7516/2020/04/034
|View full text |Cite
|
Sign up to set email alerts
|

Probing the gravitational wave background from cosmic strings with LISA

Abstract: Cosmic string networks offer one of the best prospects for detection of cosmological gravitational waves (GWs). The combined incoherent GW emission of a large number of string loops leads to a stochastic GW background (SGWB), which encodes the properties of the string network. In this paper we analyze the ability of the Laser Interferometer Space Antenna (LISA) to measure this background, considering leading models of the string networks. We find that LISA will be able to probe cosmic strings with tensions Gµ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
311
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(316 citation statements)
references
References 213 publications
(398 reference statements)
5
311
0
Order By: Relevance
“…One of such cosmological sources is the cosmic superstring network [91], which emits GWs throughout the history of the Universe, and generates a SGWB from the superposition of many uncorrelated sources, as mentioned in Introduction. Recently, it was found that LISA will be able to detect such a background with Gµ/c 2 O 10 −17 [14], while currently the most stringent bounds come from pulsar timing arrays [38], which yield the upper bound Gµ/c 2 O 10 −11 . On the other hand, depending on the string network model, LIGO-Virgo observations could constrain it to Gµ/c 2 O 10 −14 [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…One of such cosmological sources is the cosmic superstring network [91], which emits GWs throughout the history of the Universe, and generates a SGWB from the superposition of many uncorrelated sources, as mentioned in Introduction. Recently, it was found that LISA will be able to detect such a background with Gµ/c 2 O 10 −17 [14], while currently the most stringent bounds come from pulsar timing arrays [38], which yield the upper bound Gµ/c 2 O 10 −11 . On the other hand, depending on the string network model, LIGO-Virgo observations could constrain it to Gµ/c 2 O 10 −14 [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…where m M is the monopole mass and µ is the string tension. Using this decay rate and the BOS model [29] for GW emission from string loops (for a general discussion, see [3]), the SGWB generated by a metastable string network was evaluated for the parameters of the B−L model. In the LIGO-Virgo frequency band a GW signal close to the current upper limit was predicted 1 and from the PTA bounds an upper bound on the monopole-stringtension ratio was obtained, √ κ 8 [24].…”
Section: Jhep04(2021)168mentioning
confidence: 99%
“…We are interested in embedding U(1) B−L into a larger group such that B−L strings can break into segments connecting a monopole with an antimonopole. The simplest possibility is to extend the electroweak part of the standard model gauge group to SU(2 3 . Hence, the homotopy groups π 1 (M) and π 2 (M) are trivial and there are neither topologically stable monopoles nor strings.…”
Section: Jhep04(2021)168mentioning
confidence: 99%
See 1 more Smart Citation
“…However, at second sight, the production of cosmic strings after DHI could also turn into virtue; namely, if they should be unstable, which would be the case if the gauge group of our model was embedded in a semisimple GUT gauge group at higher energies [73] (see also [74,75]). This is a reasonable assumption and could lead to a promising scenario where the string network first emits an observable signal in gravitational waves [76] and then decays during the radiation-dominated era, so as to circumvent the CMB bound on Gµ cs . We will come back to such a scenario in future work.…”
Section: Introductionmentioning
confidence: 99%